A cause–effect relationship between Graves’ disease and the gut microbiome contributes to the thyroid–gut axis: A bidirectional two-sample Mendelian randomization study - Cao, Jiamin; Wang, Nuo; Luo, Yong; Ma, Chen; Chen, Zhuokun; Chenzhao, Changci; Zhang, Feng; Qi, Xin; Xiong, Wei (Frontiers in Immunology, 2023)
Background: The association between Graves’ disease (GD) and the gut microbiome has been identified, but the causal effect between them remains unclear. Methods: Bidirectional two-sample Mendelian randomization (MR) analysis was used to detect the causal effect between GD and the gut microbiome. The gut microbiome data was from multiracial samples (18,340 samples), and the GD data was from Asian samples (212,453 samples). Single nucleotide polymorphism (SNP) was selected as an instrumental variable according to different criteria and used to evaluate the causal effect between exposures and outcomes through inverse-variance weighting (IVW), the weighted median method, the weighted mode method, MR-Egger, and the simple mode weighted. F statistics and sensitivity analysis were performed to test the bias and reliability. Results: In total, 1,560 instrumental variables were extracted from the gut microbiome data (p<1×10^-5). Classes Deltaproteobacteria (OR=3.603) and Mollicutes as well as genera Ruminococcus torques group, Oxalobacter, and Ruminococcaceae UCG 011 were the risk factors for GD. Family Peptococcaceae and genus Anaerostipes (OR=0.489) were the protective factors for GD. In addition, 13 instrumental variables were extracted from GD (p<1×10^-8), causing 1 family and 8 genera to be regulated. Genera clostridium innocuum group (p=0.024, OR=0.918) and Anaerofilum (p=0.049, OR=1.584) had the greatest probability of being regulated. Significant weak bias, heterogeneity, and horizontal pleiotropy were not detected. Conclusion: A causal effect exists between GD and the gut microbiome, demonstrating a regulatory effect and interactions with each other, thus providing evidence for the thyroid-gut-axis (TGA).